Pengaturan Pengunduran Diri Anggota Negara ASEAN - Andi Jailani Sanduan; Efie Baadilla; Dyah Ridhul Airin Daties (TATOHI: Jurnal Ilmu Hukum, 2021)
Introduction: ASEAN in general is one of the international organizations in the Southeast Asian region whose initial goal was to form a peace zone in the Southeast Asian region.Purposes of the Research: Analyze and discuss arrangements regarding the resignation of member countries from ASEAN membership.Methods of the Research: The research method used in this research is normative law which is sourced from primary, secondary, tertiary legal materials, which data collection is carried out through literature studies.Results of the Research: Based on the results of this study, it is revealed that the resignation of ASEAN member countries cannot be carried out. It is clear that the Vienna Convention on the Law of Treaties 1969 stipulates that if there is no regulation regarding withdrawal from an international treaty, then the resignation cannot be carried out. However, if a country is difficult to withdraw from ASEAN or other international organizations, it can be said that the member country concerned continues to violate its obligations as a member. Therefore, it would be better to put forward the principles of the ASEAN Way as a norm for peaceful dispute resolution and emphasize deliberation and consensus